The effect of tea powder waste on the growth of capsicum annuum / Nur Zakirah Junid - Junid, Nur Zakirah (2018)
Tea powder waste is known as organic materials that can served as compost. Application of different amount of compost gives effect on the growth of Capsicum annuum. This study was conducted to observe the effect of different ratio of tea powder waste on the growth of Capsicum annuum. The tea powder waste which was locally available agro-industrial disposal was used as the treatment. The treatments were the combination of tea powder waste with soil. The ratio used were 3 tea powder compost : 1 soil ( T1) , 1 tea waste compost : 3 soil ( T2 ), 1 tea waste compost : 1 soil ( T3 ) and non-amended soil was served as control ( T4 ). Treatments were design in Completely Randomized Design (CRD) method. The results were collected from the observed parameter such as plant height, area of leaf and the number of leaf per plant. Based on the results obtained from this experiment, application of compost with ratio 1 tea powder compost: 1 soil ( T3 ) shows the highest parameter in growth. It indicates that this treatment can be used to improve the growth, yield and quality of plant.